A versatile and membrane-less electrochemical reactor for the electrolysis of water and brine. Issue 5 (6th March 2019) - H. Hashemi, S. Mohammad; Karnakov, Petr; Hadikhani, Pooria; Chinello, Enrico; Litvinov, Sergey; Moser, Christophe; Koumoutsakos, Petros; Psaltis, Demetri
Abstract : Separation of electrolysis products using fluidic inertial forces in a 3D printed flow cell. Abstract : Renewables challenge the management of energy supply and demand due to their intermittency. A promising solution is the direct conversion of the excess electrical energy into valuable chemicals in electrochemical reactors that are inexpensive, scalable, and compatible with irregular availability of electrical power. Membrane-less electrolyzers, deployed on a microfluidic platform, were recently shown to hold great promise for efficient electrolysis and cost-effective operation. The elimination of the membrane increases the reactor lifetime, reduces fabrication costs, and enables the deployment of liquid electrolytes with ionic conductivities that surpass those allowed by solid membranes. Here, we demonstrate a membrane-less architecture that enables unprecedented throughput by 3D printing a device that combines components such as the flow plates and the fluidic ports in a monolithic part, while at the same time, providing tight tolerances and smooth surfaces for precise flow conditioning. We show that inertial fluidic forces are effective even in millifluidic regimes and, therefore, are utilized to control the two-phase flows inside the device and prevent cross-contamination of the products. Simulations provide insight on governing fluid dynamics of coalescing bubbles and their rapid jumps away from the electrodes and help identify three key mechanisms for their fast and intriguing return towards the electrodes. Experiments and simulations are used to demonstrate the efficiency of the inertial separation mechanism in millichannels and at higher flow rates than in microchannels. We analyze the performance of the present device for two reactions: water splitting and the chlor-alkali process, and find product purities of more than 99% and Faradaic efficiencies of more than 90%. The present membrane-less reactor – containing more efficient catalysts – provides close to 40 times higher throughput than its microfluidic counterpart and paves the way for realization of cost-effective and scalable electrochemical stacks that meet the performance and price targets of the renewable energy sector.